2011
DOI: 10.1111/j.1365-2214.2011.01305.x
|View full text |Cite
|
Sign up to set email alerts
|

Two sides of the mirror: parents' and service providers' view on the family‐centredness of care for children with cerebral palsy

Abstract: The possibility to regularly evaluate services both from the families' and the professionals' perspectives should be part of quality development. Providing general information is a challenge for all service providers. The MPOC questionnaires can be used to highlight important areas of improvement in FCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
86
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(109 citation statements)
references
References 25 publications
16
86
1
6
Order By: Relevance
“…Este conflicto emocional conlleva la separación entre las emociones y el ejercicio de sus obligaciones como padres, lo que parece repercutir en una mayor dificultad para elaborar la pérdida con respecto al hijo ideal 7,21 , por lo que se produciría una adaptación sin tiempo para elaborar los diferentes aspectos emocionales 4,10 . En este sentido, la mayoría de los estudios basados en intervenciones en PCI, destacan la necesidad de incluir la experiencia de la familia, como el caso de los llamados "family-centredservices" 22,23 . Los padres también han señalado las consecuencias de criar a un niño con PCI, siendo lo más destacable la falta de tiempo que encuentran, así como los efectos que tiene sobre su vida social, laboral y económica.…”
Section: Discussionunclassified
“…Este conflicto emocional conlleva la separación entre las emociones y el ejercicio de sus obligaciones como padres, lo que parece repercutir en una mayor dificultad para elaborar la pérdida con respecto al hijo ideal 7,21 , por lo que se produciría una adaptación sin tiempo para elaborar los diferentes aspectos emocionales 4,10 . En este sentido, la mayoría de los estudios basados en intervenciones en PCI, destacan la necesidad de incluir la experiencia de la familia, como el caso de los llamados "family-centredservices" 22,23 . Los padres también han señalado las consecuencias de criar a un niño con PCI, siendo lo más destacable la falta de tiempo que encuentran, así como los efectos que tiene sobre su vida social, laboral y económica.…”
Section: Discussionunclassified
“…Current research suggests that weakness in communication patterns between the health care team and patients' families persists. [42][43][44][45] This contributes to a lack of empowerment and confidence about readiness for discharge 38 and provider-family conflict. 46,47 FCC practices that promote consistent communication and purposeful interaction between all individuals involved in a patient's care, such as daily updates with patients' families via real-time video conferencing, may ultimately be useful in bridging current gaps in FCC.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question of whether parents and children actively participate in the rehabilitation planning process and whether their needs are being met. Previous studies in Finland have indeed shown that the child is often left in a passive role and parents are not always fully involved in their child's rehabilitation-planning and goal-setting process [58,18,59]. The professionals in Finland have adopted the basic principles of family-centred service (FCS) [18] with the aim of enhancing family satisfaction and reducing stress related to service delivery [5,7].…”
Section: Discussionmentioning
confidence: 99%